Analysis of the calcium-phosphorus metabolism and function of the parathyroid glands in patients with type 1 diabetes mellitus - Ekaterina Alexandrovna Khantakova; Larisa Yur'evna Khamnueva; Galina Mikhailovna Orlova (Сахарный диабет)
Objective. To analyze the calcium-phosphorus metabolism in patients with diabetes mellitus (DM) type 1 depending on the functional state of the kidneys. Materials and Methods. The study involved 235 patients with type 1 diabetic (males). One hundred and thirty-four patients entered the group without diabetic nephropathy (DN) and 101 patients entered the group with DN. To study the phosphorous-calcium metabolism in patients with type 1 diabetes there were studied the following parameters in blood plasma: the level of intact parathyroid hormone (PTH), total calcium (Ca), ionized calcium (Ca2+), serum phosphorus (P), as well as calculated CaxP product. Results.  In patients with type 1 diabetes in the progression of DN the increase of P was observed from stage 4 CKD and reduction of Ca ? from CKD stage 5. The increase of the level of PTH was observed from the stage of CKD 3, although isolated cases of secondary hyperparathyroidism were registered in patients with stage CKD 2. At the same time in a large group of the patients with type 1 diabetes there was observed level of PTH below the target values of the stages CKD 3, 4, 5. The deterioration of glycemic control in patients with type 1 diabetes is associated with decreased level of PTH. In patients with type 1 diabetes without DN and with DN there was observed inverse relationship between the level of glycated hemoglobin (HbA. 1c). Conclusion. In patients with type 1 diabetes the progression of DN leads to various disorders of phosphorus-calcium metabolism: reduction of Ca, higher level of P, alter the function of the parathyroid glands (secondary hyperparathyroidism and reduction of PTH below the target value). Deterioration of glycemic control in patients with type 1 diabetes is associated with a reduction of PTH.